Total intravenous anaesthesia with ketamine, medetomidine and guaifenesin compared with ketamine, medetomidine and midazolam in young horses anaesthetised for computerised tomography. (13th December 2018) - Pratt, S.; Cunneen, A.; Perkins, N.; Farry, T.; Kidd, L.; McEwen, M.; Rainger, J.; Truchetti, G.; Goodwin, W.
Summary: Background: There is no information directly comparing midazolam with guaifenesin when used in combination with an alpha‐2 agonist and ketamine to maintain anaesthesia via i.v. infusion in horses. Objectives: To compare ketamine–medetomidine–guaifenesin with ketamine–medetomidine–midazolam for total intravenous anaesthesia (TIVA) in young horses anaesthetised for computerised tomography. Study design: Prospective, randomised, blinded, crossover trial. Methods: Fourteen weanlings received medetomidine 7 μg/kg bwt i.v. and anaesthesia was induced with ketamine 2.2 mg/kg bwt i.v. On two separate occasions horses each received infusions of ketamine 3 mg/kg bwt/h, medetomidine 5 μg/kg bwt/h, guaifenesin 100 mg/kg bwt/h (KMG) or ketamine 3 mg/kg bwt/h, medetomidine 5 μg/kg bwt/h, midazolam 0.1 mg/kg bwt/h (KMM) for 50 min. Cardiorespiratory variables and anaesthetic depth were assessed every 5–10 min. Recovery times after the infusions ceased were recorded and recovery quality was assessed using a composite score system (CSS), simple descriptive scale (SDS) and visual analogue scale (VAS). Multivariable models were used to generate mean recovery scores for each treatment and each recovery score system and provide P‐values comparing treatment groups. Results: Anaesthesia was uneventful with no difference in additional anaesthetic requirements and little clinically relevant differences in cardiopulmonary variables between groups. All horses recovered without incident with no significant difference in recovery times. Quality of the anaesthetic recovery was significantly better for the KMM group compared with the KMG group using the CSS (P<0.001), SDS (P<0.001) and VAS (P<0.001). Main limitations: No surgical stimulus was applied and study animals may not represent general horse population. Conclusion: Midazolam is a suitable alternative to guaifenesin when co‐infused with ketamine and medetomidine for anaesthesia in young horses undergoing noninvasive procedures. Both infusions produce a clinically comparable quality of anaesthesia; however, recovery from anaesthesia is of a better quality following an infusion of ketamine–medetomidine–midazolam.